Detection of Anti-LipL32 Antibodies in Serum Samples from Horses with Chronic Intraocular Infection with Leptospira spp. - Tobias Geiger; Hartmut Gerhards; Bettina Wollanke (Pathogens, 2021)
Equine recurrent uveitis (ERU) is typically caused by chronic intraocular leptospiral infection in warm-blooded horses in central Europe. The most effective therapy for leptospiral-induced ERU is the surgical removal of diseased vitreous (vitrectomy). Since vitrectomy is a highly specialized and invasive surgery, the indication must be determined very carefully. In order to obtain evidence of intraocular leptospiral infection by laboratory diagnostics in questionable leptospiral ERU-cases, sampling of aqueous humor is required, because serum tests using microscopic agglutination test (MAT) are too unspecific. The SNAP Lepto is a cross-species rapid test for the detection of anti-Lipl32 antibodies that has a high sensitivity (0.97) and specificity (1.00) for the detection of anti-leptospiral antibodies using aqueous humor or vitreous samples, which is comparable to MAT. To evaluate sensitivity and specificity of SNAP Lepto using serum, serum samples from 90 horses with confirmed leptospiral ERU and from 103 ocularly healthy horses were tested by both MAT and SNAP Lepto. Sensitivity was similar for both tests (0.82 vs. 0.79), but specificity was lower for MAT (0.52 vs. 0.95). Sensitivity and specificity are therefore lower in serum samples compared to intraocular samples, however, the SNAP Lepto is far superior to MAT and suitable as a screening method using equine serum.